The Influence of Live Streaming, Brand Awareness, and Brand Image on Purchase Interest in Shopee E-Commerce among Students of Universitas Muhammadiyah Surakarta - Revi Oktaviani Purwaningrum; Edy Purwo Saputro (Indonesian Interdisciplinary Journal of Sharia Economics, 2024)
This research provides an in-depth understanding of the factors that influence Universitas Muhammadiyah Surakarta students' buying interest in Shopee e-commerce. One of the findings shows that Live Streaming does not have a significant influence on purchasing interest on the platform. Nevertheless, an interesting finding is that Brand Awareness and Brand Image, two important aspects of brand marketing strategy, have a positive and significant influence on purchase intention. This indicates that brand awareness and image have a more dominant role in influencing purchasing decisions than live-streaming factors among students. This positive influence shows that efforts to increase awareness and build a strong brand image can be an effective strategy in increasing buying interest in Shopee e-commerce among students. Therefore, a deep understanding of how these factors interact with each other can help related parties develop more effective marketing strategies and strengthen brand positions in an increasingly competitive market.